2020
DOI: 10.1177/2280800020966938
|View full text |Cite
|
Sign up to set email alerts
|

Repair strength and surface topography of lithium disilicate and hybrid resin ceramics with LLLT and photodynamic therapy in comparison to hydrofluoric acid

Abstract: Aim: The aim was to compare the repair bond strength and surface topography of lithium disilicate ceramics (LDC) and hybrid resin ceramics (HRC) using different surface conditioning treatments [low level laser therapy (LLLT), photodynamic therapy (PDT), hydrofluoric acid (HF) with silane and air abrasion (AA) and silane]. Material and method: Sixty specimens each of LDC and HRC were used. Discs were prepared for each group (6 × 2 mm), conditioned using different regimes. Specimens in group 1 and 5 were laser i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 25 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…The failure analysis was performed using SEM and digital microscope (Hirox KH 7700, Tokyo, Japan). 4 The failure were classified as adhesive, cohesive, or admixed.…”
Section: Methods Of Cementationmentioning
confidence: 99%
See 1 more Smart Citation
“…The failure analysis was performed using SEM and digital microscope (Hirox KH 7700, Tokyo, Japan). 4 The failure were classified as adhesive, cohesive, or admixed.…”
Section: Methods Of Cementationmentioning
confidence: 99%
“…3 All these factors contribute to the reduced stiffness and fracture resistance of the tooth. 4 Therefore, restoring and retaining such compromised structure necessitates the post-placement for retention and adhesion of coronal restorations. 3,5 Traditionally, cast metal posts are used to retain core buildup on root canal treated teeth (RCT).…”
Section: Introductionmentioning
confidence: 99%
“…The lust of gloss achieved often depends upon composition, filler size, and type of surface treatment. Studies have demonstrated that materials such as LAVA Ultimate are composed of discrete and clustered nanoparticles whose size is smaller than the wavelength [12,28]. Studies have suggested that filler size smaller than light wavelength allows the reflection of light fully, without influencing the gloss effect [25].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the physiochemical fusion of the ceramic and resin matrix with varying ratios has evolved this vulnerability. The optical phenomenon of the gloss effect is achieved through a reflection of light that depends on the surface capacity and surface roughness governed by the composition [11,12]. The glassy network in ceramics has demonstrated greater power to allow reflected light to pass; hence, the aesthetic stability of the composites is lower than that of the ceramics [2,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation